PERKEMBANGAN TEKNOLOGI BATUBARA BERSIH BERWAWASAN LINGKUNGAN - Suwarna, Endang (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Coal has a very important role to meet energy demand in Indonesia, however, it is also theÃ‚Â dirtiest fuel among the fossil fuels. As coal utilization continues to increase, pollutants andÃ‚Â greenhouse gases emissions from the coal utilization also increase, that would lead toÃ‚Â environmental problems. Therefore, development of clean coal technologies for reducingÃ‚Â those emissions from coal utilization needs to be considered. The technologies areintended to reduce the policy conflict between continuing coal utilization and protectingÃ‚Â environment potential by improving the effectiveness of control technologies and reducingÃ‚Â their costs. In addition, the technologies have higher efficiency that would impact onÃ‚Â conserving fuels that lead to reducing costs and extension of coal reserve availability.